Letter from Jane Tolmach - Jane Tolmach:::::: (1970)
In this October 29, 1970 letter, Jane Tolmach informs Democratic nominees that the Women's Division of the Democratic State Central Committee will hold its annual Key Women Award party after the General Election. Nominees are invited to recommend women volunteers to receive a gold key pin in recognition of their campaign work. The event will take place in early December or January, and nominees will be asked to submit names and addresses shortly after the election.